Analisis pola asuh orang tua terhadap motivasi belajar siswa di UPT SDN 2 Rantau Tijang Kecamatan Pardasuka - Afriyandi Afriyandi; Herpratiwi Herpratiwi; Nurlaksana Eko Rusminto (ARKA INSTITUTE, 2022)
Education is something that cannot be separated in human life. Likewise, parenting patterns for children's growth and development are very decisive for their growth and development, especially in shaping the personality of children who have high motivation. This is because parents are the first environment for children so that the child's personality depends on their upbringing. The research method used is qualitative, it is intended to know clearly in analyzing natural objects, where the researcher is the key instrument. While the data analysis technique used is a data triangulation technique in the form of a merging technique which is carried out using detailed analysis of the research subject. The result of this research is that there is an effect of parenting style on students' learning motivation in class. 4) In the text